Vimala Devi's Bhatcars and the Mundcars: Laborers, Landlords, and Culture in Goa - Menezes, Dale Luis (Archīum Ateneo, 2024)
The master-servant, or broadly bhatcar-mundcar, relations are fundamental to Goan culture, history, and society. While the interaction of these two broad socio-economic groups, those who labor and those who do not, was and is fundamental to Goan politics, scholars have not yet evolved a methodological framework for understanding these relations. This absence, the paper claims, is a particularly serious problem for Goa studies, and one that can be tackled by thinking closely about categories such as bhatcar and mundcar. The terms bhatcar and mundcar are defined capaciously, making room for a range of servitudes and labor regimes as well as different ways in which the masters live as bhatcars and the servants as mundcars. This paper uses Vimala Devi’s Monsoon to formulate broad generalizations about the master-servant relations in Goa. The paper engages with the historiography of labor and caste in South Asia as well as Goan historiography to deepen the understanding of labor relations and culture in Goan society.